TAX ANALYSIS: THEORETICAL FOUNDATIONS, INTERNATIONAL EXPERIENCE, AND PRACTICAL APPROACH ON THE EXAMPLE OF UZBEKISTAN (World Economics and Finance Bulletin, 2026)
The paper provides an in-depth examination of key issues such as methodologies for assessing tax system efficiency, the impact of tax burden on economic growth, and the fiscal effectiveness of tax incentives. Special attention is given to the large-scale tax reform implemented in the Republic of Uzbekistan since 2017. Based on a comparison of Uzbekistan’s tax burden with OECD countries and developing economies, several strategic recommendations are proposed. The findings indicate that the ongoing tax reforms in Uzbekistan contribute to the stabilization of budget revenues and the stimulation of economic growth; however, challenges remain in the areas of tax administration and ease of tax compliance.
Keywords: Uzbekistan tax system; tax analysis, fiscal policy, tax burden, tax efficiency, taxpayers, tax incentives